Gray Triggerfish Reproductive Biology, Age, and Growth off the Atlantic Coast of the Southeastern USA. Issue 3 (30th March 2017) - Kelly‐Stormer, Amanda; Shervette, Virginia; Kolmos, Kevin; Wyanski, David; Smart, Tracey; McDonough, Chris; Reichert, Marcel J. M.
Abstract: The Gray Triggerfish Balistes capriscus supports fisheries on both sides of the Atlantic Ocean. We utilized fishery‐independent samples to assess the age structure, growth, sex ratio, size and age at maturity, spawning season, and spawning frequency of the Gray Triggerfish population off the southeastern U.S. Atlantic coast. From 1991 to 2012, 7, 685 samples were collected, ranging in FL from 82 to 578 mm and ranging in age from 0 to 13 years. Our study provides key life history information for an exploited population and is the first to comprehensively describe age, growth, and reproduction for a Balistes species. We documented that the Gray Triggerfish is sexually dimorphic, with adult males attaining larger sizes at age and a larger maximum size than females. Sex‐specific growth curves were fitted, yielding the following von Bertalanffy equations: FL t = 419[1 – e –0.54( t + 0.61) ] for males and FL t = 352[1 – e –0.94( t + 0.22) ] for females. This species is characterized by a medium size at maturity (the smallest mature female was 179 mm FL; the smallest mature male was 183 mm FL) and relatively early age at maturity (the youngest mature female and male were age 0). Some shifts in population attributes coincided with a period of increased fishing pressure. Due to tighter regulations on snapper and grouper fisheries, the Gray Triggerfish has become a more targeted species. Fisheries biologists and managers should continue to evaluate potential impacts and establish management regulations that consider the region‐specific reproductive season, size and age at maturity, and sex‐specific differences in growth documented in this study. Received April 20, 2016; accepted January 9, 2017 Published online March 30, 2017